2021
DOI: 10.1021/acs.nanolett.0c04667
|View full text |Cite
|
Sign up to set email alerts
|

Can Copper Nanostructures Sustain High-Quality Plasmons?

Abstract: Silver, king among plasmonic materials, features low inelastic absorption in the visible-infrared (vis-IR) spectral region compared to other metals. In contrast, copper is commonly regarded as too lossy for actual applications. Here, we demonstrate vis-IR plasmons with quality factors >60 in long copper nanowires (NWs), as determined by electron energy-loss spectroscopy. We explain this result by noticing that most of the electromagnetic energy in these plasmons lies outside the metal, thus becoming less sensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…To the best of our knowledge, such a range of operating wavelengths has never been reported for an optical antenna. Note that in the mid-IR, aluminum behaves as an almost perfect Drude metal, with surface plasmon resonances exhibiting a more “photon-like” behavior—similar to what was observed for copper nanostructures in the IR ( 31 ).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…To the best of our knowledge, such a range of operating wavelengths has never been reported for an optical antenna. Note that in the mid-IR, aluminum behaves as an almost perfect Drude metal, with surface plasmon resonances exhibiting a more “photon-like” behavior—similar to what was observed for copper nanostructures in the IR ( 31 ).…”
Section: Resultsmentioning
confidence: 53%
“…This might be problematic in EELS, as low energy resonances are convoluted with the so-called “zero-loss peak” (ZLP), which is associated with the elastic scattering of the electrons ( 30 ). In this work, we use a highly monochromated electron microscope, having demonstrated its capability to probe surface plasmons ( 31 ) and phonons ( 32 ) up to the far-IR.…”
mentioning
confidence: 99%
“…Understanding oxidation processes and the corresponding mechanisms involved is paramount for the design, synthesis and fabrication of technologically relevant metal nanostructures 1,2 . Focusing on Cu, its nanoparticles both in metallic and oxide forms are attractive for applications within electronics 3,4 , photonics 5,6 , catalysis 7,8 and nanomedicine 8 , owing to Cu's unique physical and chemical properties, and relatively high abundance. However, applications of metallic Cu particles are limited due to their chemical instability at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The few existing in situ single particle studies using scanning transmission electron microscopy (STEM) 32 and plasmonic nanospectroscopy 33 are limited in that the former was executed at very low oxygen pressures, and the latter is blind to morphological details. Here, we address these challenges by recording in situ the morphological and compositional evolution of single Cu nanoparticles using annular dark-field STEM (ADF STEM) imaging, and by simultaneously probing the evolution of their localized surface plasmon resonances (LSPR) using electron energyloss spectroscopy (EELS) 6,[34][35][36] in an environmental TEM (ETEM) 37 (Fig. S1), in analogy to the bulk plasmon studies of hydride formation in Pd nanocrystals 38 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fedyanin et al demonstrated ultralow-loss Cu plasmonic waveguides, [43] and Mkhitaryan et al showed that Cu nanostructures could support high-quality plasmons. [46] Although impressive progress has been made toward improving the properties of plasmonic components, integration of different plasmonic components in electronic-plasmonic transducers is rare. For example, ultrafast temporal modulation (>1 GHz) of light emission, [15] directional plasmon excitation, [23,47] or highly efficient plasmon excitation [48] has been demonstrated for tunnel junctions equipped resonant structures.…”
Section: Introductionmentioning
confidence: 99%